Development Development of Excel-Based Learning Media to Improve Understanding of High School Statistical Concepts - Zainul Chusna; Caswita Caswita; Een Yayah Haenilah (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2022)
The development of this product aims to facilitate teachers and students in learning statistics to be more efficient so as to achieve completeness in terms of understanding students' mathematical concepts. The product developed was validated by experts and the results showed that the product was in the valid and feasible category to be applied in learning. Furthermore, limited trials were carried out on several students and teachers to see the practicality of the product, getting the results that the product developed was classified as very practical. The research was continued by testing this product in learning. The sample for this product trial was selected by purposive sampling. This research design uses a pretest-posttest control group design with 2 classes consisting of an experimental class using excel-based media and a control class using conventional learning. Hypothesis testing using the t-test showed that at the time of the pretest there was no difference in average between the two classes, while at the posttest there was an average difference between the two classes. Followed by the N-Gain test to see the average increase between the pretest and posttest results from the two classes showing the results that the average increase in understanding mathematical concepts in the experimental class is higher than the average increase in understanding mathematical concepts in the control class. So it can be concluded that the product developed is valid, practical, and effective in increasing students' understanding of mathematical concepts.